A sociedade contemporânea e a configuração da educação moçambicana - Maurício Sapane, Benedito (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Based on the socio economic conjunture that Mozambique crossed or crosses from the period of independence (1975) until the present days (nowadays), neglect on the problematics of contemporary education, trying to bring differents opinions that can help to reflect a school raised by Anisio Teixeira. For the reflection hermeneutics combinations are made in order to construct a historical and philosofical thought about the contemporary mozambicanschool .
Keywords: Flexibility; Marxism